Exploring the Coverage of Climate Change Issue in Pakistani Media - Riffat; Dr. Amrat Haq (Journal of Peace, Development and Communication, 2022)
This study examines editorial coverage of climate change in leading Pakistani newspapers at an interesting time when the country is devising adaptation and mitigations plans in the wake of growing environmental challenges. Based on Van Dijk’s discursive strategies (Van Dijk, 2005), this study used critical discourse analysis to comparatively examine the predominant themes in editorial coverage of elite newspaper, The daily Dawn, The News International and The Express Tribune resulting in two themes of ‘Climate Change vulnerability’ and ‘Climate Change governance’. While all newspapers highlighted themes of ‘of ‘Climate Change vulnerability’ in their editorial coverage, there was appreciation regarding climate change governance in the editorials of The News International and The Express Tribune but The daily Dawn was skeptical, cynical and negative towards role of governance regarding climate change in Pakistan.